A signal cascade amplification strategy based on RT-PCR triggering of a G-quadruplex DNAzyme for a novel electrochemical detection of viable Cronobacter sakazakii. Issue 13 (11th May 2020) - Yuan, Yuanyuan; Wu, Xianyong; Liu, Zhanmin; Ning, Qiqi; Fu, Liqiang; Wu, Sujuan
Abstract : An effective and sensitive DNAzyme method for electrochemical detection of viable Cronobacter sakazakii was designed. The detection method is based on RT-PCR and cascade amplification of ribozymes to achieve rapid detection of viable Cronobacter sakazakii. Abstract : Cronobacter sakazakii is an important opportunistic food-borne pathogen, and it can cause severe diseases with main symptoms including neonatal meningitis, necrotizing enterocolitis, and sepsis. For the achievement of practical and convenient detection of viable C. sakazakii, a simple and robust strategy based on the cascade signal amplification of RT-PCR triggered G-quadruplex DNAzyme catalyzed reaction was firstly used to develop an effective and sensitive DNAzyme electrochemical assay. Without viable C. sakazakii in the samples there are no RT-PCR and DNAzyme products, which can cause a weak electrochemical response. Once viable C. sakazakii exists in the samples, an obvious enhancement of the electrochemical response can be achieved after the target signal is amplified by RT-PCR and the resulting DNAzyme, which catalyze the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) by H2 O2 with the assistance of the cofactor hemin. Our novel assay can be performed in a range of 2.4 × 10 7 CFU mL −1 to 3.84 × 10 4 CFU mL −1 ( R 2 = 0.9863), with a detection limit of 5.01 × 10 2 CFU mL −1 . Through the assay of 15 real samples, electrochemical detection assay provided the same results as conventional detection methods. Therefore, detection of viable C. sakazakii based on G-quadruplex DNAzyme electrochemical assay with RT-PCR demonstrates the significant advantages of high sensitivity, low cost and simple manipulation over existing approaches and offers an opportunity for potential application in pathogen detection.